1987
DOI: 10.1073/pnas.84.11.3723
|View full text |Cite
|
Sign up to set email alerts
|

Soluble factors stimulating secretory protein translocation in bacteria and yeast can substitute for each other.

Abstract: mRNA for prepro-a--factor (ppc), a yeast secretory glycoprotein, was translated in a wheat germ cell-free system that was posttranslationally supplemented either with inverted vesicles from the plasma membrane ofEscherichia coli (INV) or with microsomes from Saccharomyces cerevisiae. A postribosomal supernatant (PRS) from E. coli was found to stimulate translocation of ppa across the INV membrane. A yeast PRS could substitute for its E. coli counterpart. Likewise, an E. coli PRS could substitute for a yeast PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…A larger (12S) putative targeting factor was characterized several years ago from E. coli and also did not appear to contain RNA (22). Recent evidence (6) suggests that the bacterial and yeast factors which stimulate secretory protein transport can substitute for each other and thus may be functionally related. Their roles in this process remain to be elucidated, but their differences in structure and localization (see above) suggest that they do not act via a mechanism similar to SRP.…”
Section: Discussionmentioning
confidence: 99%
“…A larger (12S) putative targeting factor was characterized several years ago from E. coli and also did not appear to contain RNA (22). Recent evidence (6) suggests that the bacterial and yeast factors which stimulate secretory protein transport can substitute for each other and thus may be functionally related. Their roles in this process remain to be elucidated, but their differences in structure and localization (see above) suggest that they do not act via a mechanism similar to SRP.…”
Section: Discussionmentioning
confidence: 99%
“…(or to contain either an inactive form or a negligible amount of) all those cytosolic factors that have so far been shown to be involved in protein translocation across microsomal membranes (Walter and Blobel, 1980;Fecycz and Blobel, 1987;Chirico et al, 1988). In fact, we show here that nuclear-encoded mitochondrial proteins, when synthesized in a wheat germ system, are not imported into yeast mitochondria to a significant extent unless a yeast postribosomal supernatant (PRS) ~ is added to the import reaction.…”
mentioning
confidence: 75%
“…RRL and WGE translation kits; Promega) since yeast is not a typical animal or a plant. Furthermore, it has been reported that the cell lysate from different systems exhibits importstimulating activity [25][26][27][28][29]. The potential influence of such stimulating factors may partly account for the unusual import of Mtf1p.…”
Section: Import Of Mtf1p Derivatives Synthesized In the Rrl Or Wge Trmentioning
confidence: 99%